Pengaruh Kompres Hangat terhadap Suhu Tubuh Anak dengan Demam Berdarah Dengue (DBD) di Rumah Sakit Umum Daerah Deli Serdang Lubuk Pakam - Arfah May Syara; Syatriawati Syatriawati; Pitriani Pitriani; Grace Erlyn Sitohang (STIKes Santa Elisabeth Medan, 2021)
Background: Based on the results of initial observations or observations made by researchers in the Kenanga Room of RSUD Deli Serdang Lubuk Pakam, it was found that the number of DHF sufferers in children from January to December was found to be 174 people aged <1 year to 14 years. And from January to March, it was found that there were 67 people aged 1-11 months to 14 years. The purpose of this study was to determine the effect of warm compresses on body temperature in children aged 5-12 years with dengue fever in the Kenanga room at Deli Serdang Hospital, Lubuk Pakam.Methods: This type of research is a quasi-experimental research design with a times series design. Research time is planned in June. The sampling technique was carried out by accidental sampling. The number of samples obtained is 8 people.Results: After doing the research, it was found that the average pretest measurement was 38.7°C while the posttest was 37.1°C. With a significant p value of 0.03 which is lower than a significant value of 0.05, which means that Ho is rejected, it means that there is an effect of warm compresses on decreasing body temperature in children aged 5-12 years with dengue fever in the memory room of the Deli Serdang Regional General Hospital. Lubuk Pakam.Conclusion: Based on the results above, it is recommended that the room nurse take warm compresses to help reduce the body temperature of children with DHF during treatment in the hospital.